Comparative high mountain research on the treeline ecotone under human impact Carl Troll’s Asymmetrical Zonation of the Humid Vegetation Types of the World of 1948 reconsidered: Carl Troll’s "Asymmetrical Zonation of the Humid Vegetation Types of the World" of 1948 reconsidered - Miehe, Georg; Miehe, Sabine (ERDKUNDE, 2000)
50 to 40 years after C. Troll’s concepts on the ’Asymmetrical Zonation of the Humid Vegetation Types’ and ’the Tropical Mountains’ it has become evident that quasi natural and heavily human-interfered treelines had been amalgamated. Isolated fruiting and regenerating trees in zonal habitats of a quasi-alpine environment above the present upper forest border witness the potential natural presence of forest. The high-altitude grassland of the Páramo or equivalent dwarf-shrub formations up to at least 4,100 m a. s. l. are supposed to be a replacement vegetation induced and maintained by fire used by man to obtain open pastures or for hunting purposes. Thus, the innertropical treeline is lowered artificially by 500 to 600 m. In Troll’s figure of 1948 the treelines of mountains of the northern hemisphere are drawn 800 to 1,300 m too high and those of the southern hemisphere 500 to 800 m too low. Troll’s concept to classify forests of subtropical mountains as altitudinal equivalent of high latitude vegetation formation is misleading, because the dominant treeline species are differing Larix, Pinus and Picea of high latitude versus Juniperus and Abies as subtropical upper treeline constituents. The presence of epiphytes suggests the classification as cloud forests. Considerations upon the structure of a treeline ecotone without human interference are highly hypothetical, because nearly all accessible treelines are influenced by man-induced fire, grazing or wood-cutting. Few examples from possibly natural sites show a disintegration from closed forests into isolated stands of single trees in a completely closed cover of evergreen shrubs. Most treeline constituents show transitions from tree to dwarf-shrub under natural conditions as well as in disturbed sites. In arid environments it is even more difficult to estimate the potential natural structure of the treeline ecotone, because open dwarf-forests had been widely destroyed.